Diversity and composition of rhizospheric soil and root endogenous bacteria in Panax notoginseng during continuous cropping practices. (6th January 2017) - Tan, Yong; Cui, Yinshan; Li, Haoyu; Kuang, Anxiu; Li, Xiaoran; Wei, Yunlin; JI, Xiuling
Abstract : Rhizobacteria and endophytic bacteria play important roles in protecting host plants from infection by phytopathogens, which cause soil‐borne diseases and severely impair plant health. Panax notoginseng is negatively affected by continuous cropping and becomes vulnerable to attack by microbial pathogens. In the present study, culture‐independent Illumina MiSeq was used to investigate root‐endophytic and rhizospheric bacteria in response to continuous cropping of P. notoginseng . Numbers of rhizospheric bacteria decreased with continuous P. notoginseng cropping, while the effects of continuous cropping on endophytic bacteria were not statistically significant. Bacterial diversity was higher in healthy P. notoginseng rhizospheric soils and roots than in those of diseased P. notoginseng . The most dominant phyla detected during continuous cropping were Proteobacteria, Cyanobacteria, Actinobacteria, and Acidobacteria . The genera Pseudomonas, Rhodoplanes, Candidatus Solibacter, and Streptomyces were dominant in P. notoginseng rhizospheric soils and roots. Erwinia, Stenotrophomonas, Pseudomonas, and Sphingobium were specifically detected in relatively high proportions among root‐rot rhizospheric bacteria and endogenous root bacteria in plants under continuous cropping, suggesting that they may be the pathogens responsible for the negative effects of continuous cropping on P. notoginseng . Based on canonical correspondence analysis of the bacterial communities that were identified from healthy plants and fallow soils, total phosphorus (P), pH, and organic soil matter exerted the greatest impacts upon bacterial community composition during continuous cropping. In general, continuous cropping practices for P. notoginseng and severe root‐rot disease notably affected the community structure and the diversity of rhizospheric and root endophytic bacteria. Our study elucidated the ecological significance of microbial communities in healthy plant maintenance, and our results may inform biological control strategies during the continuous cropping of P. notoginseng .